Residual impact in soybean- wheat system under irrigated condition of Bundelkhand - Singh, Narendra; Kushwaha, H. S. (Annals of Agricultural Research, 2014)
A field experiment was conducted at Tulsi KVK Ganivan, Chitrakoot (UP) during 2006-07 and 2007-08 to assess the residual effect of organic and inorganic fertilizers on wheat (Triticum aestivum). Residual effect of organic manures and inorganic fertilizers which were used in previous soybean crop with 100%NPK to wheat have significantly increased growth attributes, viz. plant height, plant dry matter and effective tillers/meter row length in wheat. Seed (4.94 and 4.95 t/ha) and straw (4.95 and 5.04 t/ha) yields, net monetary return (Rs. 42,479 and 48,213) and return/rupee invested (Rs. 4.57 and 4.48) were obtained significantly higher under residual effect of FYM 10 t/ha + 50% NPK and direct effect of 100% NPK. Similarly, nutrient uptake in terms of N, P and K were also found greatest under this treatment combination. After completion of two year sequence of soybean -wheat, fertility balance in terms of net available N, P and K in the soil was analysed. The maximum and positive fertility balance was recorded under 100% NPK through fertilizer + 5 tonnes FYM/ha in soybean crop and 100% NPK to wheat crop